OPTIMALISASI STRATEGI SOCIAL MEDIA MARKETING UNTUK MENINGKATKAN BRAND AWARENESS DI KUBU BARAT CAMP - Immellia Novitasari Vitandi; Slamet Slamet (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2025)
In the digital era, social media has become an effective marketing tool, especially for the outdoor equipment rental industry. Kubu Barat Camp, an MSME operating since 2016 in Malang, faces challenges in increasing brand awareness on social media platforms despite having relevant products and a strategic location. With more than 3.6 billion social media users, the opportunity to reach a wider audience is huge, but this potential has not been optimally utilized by Kubu Barat Camp. This study aims to explore the optimization of social media as a marketing tool to increase brand awareness. The research method used is qualitative, with data collection through interviews, documentation, and observation. The results of the study indicate the need for improved social media marketing strategies, including content variations such as video tutorials and customer stories, as well as expanding the use of other platforms such as TikTok and Facebook. More structured team management and budget allocation for promotions are also very important. With these steps, Kubu Barat Camp can more effectively build emotional connections with customers and increase their brand awareness.